Spinal anesthesia: the new gold standard for total joint arthroplasty? - Matsen Ko, Laura; Chen, Antonia F. (Annals of Translational Medicine, 2015)
The study by Basques et al. is one in a series of studies that have demonstrated that regional anesthesia is more advantageous than general anesthesia for total hip arthroplasty (THA) patients. Previous studies have shown a multitude of advantages including decreased cost, complications, infections and improved pain control. A randomized study comparing 40 patients found that total costs per case were reduced by almost half in the spinal anesthesia group compared to the general anesthesia group. This was a result of both lower cost for anesthesia and lower cost for recovery. In the same study, there were no relevant differences in anesthesia times, and patients who received general anesthesia had higher postoperative pain scores and needed more analgesics than patients in the spinal anesthesia group. Complications are reduced in spinal anesthesia, as a meta-analysis of ten independent trials found a significant decrease in deep vein thrombosis, pulmonary emboli, surgical time, and blood transfusion compared to general anesthesia in THA patients. Another study similarly found a 25% decrease in intraoperative blood loss and 50% reduction of intraoperative transfusion, with 20% lower total transfusion requirements in spinal anesthesia patients. General anesthesia has been associated with higher risk of surgical site infection and perioperative hyperglycemia in comparison to spinal anesthesia.